2016
DOI: 10.1016/j.cardfail.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Dyspnea in Chronic Heart Failure

Abstract: The experience and report of dyspnea in HF is determined foremost by somatic symptoms of psychologic distress, being of older age, being overweight, and having comorbid COPD, with disease severity and systemic inflammation levels playing an ancillary role. These findings suggest that psychologic distress should be considered when treating dyspnea complaints in patients with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 40 publications
3
24
0
8
Order By: Relevance
“…[30][31][32] Cardiac decompensation and lung oedema and directing them or not often depends on whether the patients appear in the earlier or the later stages of the disease. 24,33 Certain number of patients has dyspnoeic difficulties because of an earlier diagnosed or undiagnosed psychiatric disorder. 34 Their differentiation is made even harder by the fact that because of hyperventilation they often have tachycardia and tachypnoea in their report, sometimes even auscultatory wheezing or even hypertension because of the anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32] Cardiac decompensation and lung oedema and directing them or not often depends on whether the patients appear in the earlier or the later stages of the disease. 24,33 Certain number of patients has dyspnoeic difficulties because of an earlier diagnosed or undiagnosed psychiatric disorder. 34 Their differentiation is made even harder by the fact that because of hyperventilation they often have tachycardia and tachypnoea in their report, sometimes even auscultatory wheezing or even hypertension because of the anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, not all scales have an established minimal clinically important difference PLOS ONE [23] and it may be difficult to capture a meaningful change in dyspnea with the current scales available [4,5]. Finally, psychological and emotional distress has been significantly associated with dyspnea in HF [24,25] but these components or alterations of sensorial quality are usually nor assessed in the most commonly scales used for dyspnea assessment [6]. Accordingly, it is not surprising that many HF drug studies that have dyspnea relief as end points have failed to show a difference between the active drug and placebo.…”
Section: Discussionmentioning
confidence: 97%
“…One study found that the somatic symptoms of depression and anxiety are the strongest determinants of dyspnea. Dyspnea is also significantly associated with factors such as older age, chronic obstructive pulmonary disease (COPD), body mass index (BMI) and inflammatory factors such as interleukin‐6 and 10 (Kupper et al, ). Dyspnea can exacerbate fatigue in patients with HF by restricting their daily activities (Tsai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dyspnea is a hallmark symptom of HF (Kupper, Bonhof, Westerhuis, Widdershoven, & Denollet, 2016). In a study conducted on patients with HF, the incidence of severe dyspnea was reported as 69% (Perez- Moreno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%